Synthesis of novel heterocyclic compounds based on rational design and evaluation of their antitumor and antiangiogenic potential in human endothelial and tumor cell lines with tyrosine kinase membrane receptors as targets - Machado, Vera Alexandra Pereira (2016)
Tese de Doutoramento em Ciências - Especialidade em Química